Management of patients with combined arterial hypertension and aortic valve stenosis: a consensus document from the Council on Hypertension and Council on Valvular Heart Disease of the European Society of Cardiology, the European Association of Cardiovascular Imaging (EACVI), and the European Association of Percutaneous Cardiovascular Interventions (EAPCI). Issue 3 (30th April 2020) - Mancusi, Costantino; de Simone, Giovanni; Brguljan Hitij, Jana; Sudano, Isabella; Mahfoud, Felix; Parati, Gianfranco; Kahan, Thomas; Barbato, Emanuele; Pierard, Luc A; Garbi, Madalina; Flachskampf, Frank A; Gerdts, Eva
Abstract: Aortic valve stenosis (AS) is the third most common cardiovascular disease. The prevalence of both AS and arterial hypertension increases with age, and the conditions therefore often co-exist. Co-existence of AS and arterial hypertension is associated with higher global left ventricular (LV) pressure overload, more abnormal LV geometry and function, and more adverse cardiovascular outcome. Arterial hypertension may also influence grading of AS, leading to underestimation of the true AS severity. Current guidelines suggest re-assessing patients once arterial hypertension is controlled. Management of arterial hypertension in AS has historically been associated with prudence and concerns, mainly related to potential adverse consequences of drug-induced peripheral vasodilatation combined with reduced stroke volume due to the fixed LV outflow obstruction. Current evidence suggests that patients should be treated with antihypertensive drugs blocking the renin–angiotensin–aldosterone system, adding further drug classes when required, to achieve similar target blood pressure (BP) values as in hypertensive patients without AS. The introduction of transcatheter aortic valve implantation has revolutionized the management of patients with AS, but requires proper BP management during and following valve replacement. The purpose of this document is to review the recent evidence and provide practical expert advice on management of hypertension in patients with AS.